Analysis of combined extrusion micro coining process to manufacture microstructured tappets - Zahner, Michael; Merklein, Marion (Procedia Manufacturing, 2018)
In times of enhanced functional integration of machine elements the combination of forming processes offers an opportunity to increase the efficiency of the manufacturing process. Due to mutual interactions combining different forming operations a comprehensive analysis of the processes is necessary especially regarding micro forming processes. Within this study a combined extrusion micro coining process to manufacture microstructured tappets was investigated. The results reveal that the achieved homogeneity on tappet surface is mainly influenced by the microstructure layout applied on the tool components, due to locally widely varying material flow in the coining region.
LFT Import::2019-07-29 (2334)
Keywords: Combined forming process; Geometrical accuracy; Micro Coining; Microstructures; Tribology

Analysis of Production Limits in Manufacturing of Micro Coined Structures - Zahner, Michael; Andreas, Kolja; Engel, Ulf; Merklein, Marion (ASPEN/ASPE 2017 Spring Topical Meeting - Manufacture and Metrology of Structured and Freeform Surfaces for Functional Applications, 2017)
LFT Import::2019-08-05 (2225)

Design, Manufacturing and Tribological Performance of Microtextured Bucket Tappets for Friction Reduction in the Valve Train - Marian, Max; Zahner, Michael; Tremmel, Stephan; Andreas, Kolja; Merklein, Marion; Wartzack, Sandro (6th World Tribology Congress, 2017)
In order to improve lubricating conditions as well as friction and wear behavior, the surfaces of contacting bodies in lubricated tribological contacts can be microtextured. While this approach has already reached industrial application for lower loaded contacts, the effects for higher loaded contacts, where elastic deformation plays a significant role, are still topic of basic research. For this reason, microtextures are adapted to the conditions of the tribological system of the bucket tappet/camshaft contact in the valve train as a demonstrator and major contributor to combustion engine losses. The tribological performance of various microtexture geometries and arrangements is analyzed on a one bucket tappet/one cam test-rig using series production valve train parts. A resistive measurement system is first applied to the highly dynamic tappet/camshaft contact and allows the investigation of the correlation between lubricating conditions and friction force. In the tests, a significant friction force reduction using microtextured surfaces compared to polished surfaces is achieved. Additionally, quantitative ex-situ wear characterization is carried out for long-run test cycles, using Laser Scanning Microscopy. Thus, wear mechanisms and rates are compared with the measurements of lubricating conditions and friction force. Besides the identification of advantageous microtexture geometries and arrangements regarding the tribological performance, possibilities and limitations of the manufacturing technology are examined. In order to realize high-volume production, a micro coining process was studied. In this regard the manufacturing of the coining punch using µEDM and the coining process itself were analyzed with respect to accuracy and reproducibility. Additionally, the durability of the pins was investigated for the micro coining process. The limitations of the manufacturing process and of the micro coining process are summarized in a process windo
Keywords: Microtextures; Micro Coining; EHL Contact

Friction reduction in EHL contacts by surface microtexturing – tribological performance, manufacturing and tailored design - Tremmel, Stephan; Marian, Max; Zahner, Michael; Wartzack, Sandro; Merklein, Marion (Industrial Lubrication and Tribology, 2019)
Purpose – This paper aims to derive tailor-made microtextures for elastohydrodynamically lubricated (EHL) contacts under consideration of manufacturing possibilities. Design/methodology/approach – Component tests were used for the evaluation of the influence of surface texturing on the friction behavior in the cam/tappet contact. Furthermore, the manufacturing possibilities and limitations of a combined mEDM and micro coining process and the feasibility of integration into a forming process were studied. Finally, a methodology based on transient EHL simulations and a meta-model of optimal prognosis was exemplarily used for microtexture optimization. Findings – It was found that surface texturing in EHL contacts with high amount of sliding is promising. Moreover, the combination of mEDM and micro coining and the integration into established production processes allow the manufacturing of microtextures with desirable structural parameters and sufficient accuracy. Originality/value – This paper gives a holistic view on surface microtexturing over several phases of the product life cycle, from the design, over efficient manufacturing to application-related testin
Keywords: Friction; Elastohydrodynamic lubrication; Micro coining

Investigation of Production Limits in Manufacturing Microstructured Surfaces Using Micro Coining - Zahner, Michael; Lentz, Lukas; Steinlein, Felix; Merklein, Marion (Micromachines, 2017)
The application of microstructured surfaces is one possible method to reduce friction in lubricated contacts between components with relative movement. Due to this, the energy efficiency and the occurring wear during the operating time of the final products could be decreased. To manufacture structured surfaces economically, a micro coining process was analyzed within this study. This process offers the potential for integration into the established manufacturing processes of different final products, such as tappets used in a valve train. Thus, large-scale production is enabled. To detect the manufacturing limits of the micro coining process, the manufacturing of the coining tools as well as the coining process needs to be investigated. Within this study, the achievable accuracy and the failure of cuboid and cylindrical microstructure elements with selected dimensions were analyzed. For both types of microstructures, the minimal lateral dimensions were detected. Besides the achievable accuracy, correlations between different geometrical dimensions of the micro elements are presented. Additionally, the aspect ratio is detected as the main cause of failure for the micro coining process. In general, the suitability of a coining process for manufacturing microstructured surfaces is proven.
LFT Import::2019-07-29 (2277)
Keywords: Geometrical accuracy; Microstructures; Tribology

Kräfte-und Belastungsermittlung: Bei der Handhabung von Statorblechpaketen in der Fertigung von Elektromotoren - Schneider, Michael; Zahner, Michael; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2015)
Due to the proven low shear stress and its favorable allocation in the contact area between the individual sheets, the adhesive bonding process or baked enamel process represent packaging technologies with good electromechanical properties. For each individual application, it remains to weigh whether the lower eddy current losses justify the higher energy and time which is needed by using adhesive bonding or baked enamel. From a purely mechanical point of view, there are no concerns about the rigidity of the lamination stack during the handling process.
CRIS-Team Scopus Importer:2023-03-07

Reibungsreduzierung in EHD-Kontakten durch mikrostrukturierte Bauteiloberflächen - Auslegung, Gestaltung und umformtechnische Herstellung - Tremmel, Stephan; Marian, Max; Zahner, Michael; Weschta, Martin; Engel, Ulf; Wartzack, Sandro; Merklein, Marion (58. Tribologie-Fachtagung. 2017, Son-derband Abschlusskolloquium „Ressourceneffiziente Konstruktionselemente“ SPP 1551 der DFG, 2017)
Gezielt eingebrachte, definierte Oberflächenmikrostrukturen bieten in elastohydrodynamischen (EHD) Kontakten Potential zur Reibungsreduzierung und können damit die Energieeffizienz technischer Systeme erhöhen. Um die größtmögliche Wirksamkeit zu erreichen, sind diese Oberflächenmikrostrukturen auf die jeweilige Anwendung abzustimmen. Die Realisierung theoretisch genauer Mikrostrukturen ist zudem durch die Fertigungstechnik limitiert. Des Weiteren bestimmt das Verschleißverhalten der Mikrostrukturen im Einsatz die Bauteillebensdauer. Für einen wirksamen Einsatz über den gesamten Produktlebenszyklus hinweg bedarf es somit eines grundlegenden Verständnisses der Zusammenhänge zwischen Gestaltung, Herstellung und Einsatzverhalten oberflächenstrukturierter Bauteile. Vor diesem Hintergrund werden im vorliegenden Beitrag ein Simulationsansatz zur Untersuchung der Wirkweise von Oberflächenmikrostrukturen vorgestellt sowie eine Methodik abgeleitet, die die systematische Auslegung und Gestaltung von Oberflächenstrukturen erlaubt. Die Methodik erlaubt die Berücksichtigung individueller tribologischer Belastungskollektive und fertigungstechnischer Restriktionen. Die Fertigungsrestriktionen bei der Strukturerzeugung wurden im Hinblick auf industrielle Maßstäbe für einen Mikroprägeprozess ermittelt. Auf Basis tribologischer Untersuchungen auf einem Nocken/Stößel-Komponentenprüfstand erfolgt die Beurteilung des Reibungs- und Verschleißverhaltens der mikrostrukturierten Bauteil
LFT Import::2019-08-05 (2259)
Keywords: Elastohydrodynamik; Mikrostrukturen; Mikroprägen